A Novel Design of Automatic Grass Cutter Machine - Roy, Kousik; Chatterjee, Deep Chatterjee; Sadhu, Ankit; Kumar Rana, Dharmendra; Nandy, Madhurima; Suman, Divya (International Journal of Computer Sciences and Engineering, 2025)
At present we are having grass cutter machines that controls manually by humans and after cutting grasses, again they have to give their efforts to collect the grasses from the field. The machines which are used to cut grasses are operated on diesel, which is a wastage of natural resources. So we make a machine that cut the grasses and at the same time it collects all the grasses by vacuum cleaner. The machine is operated on battery which is charged by using solar cell. The main features of the machine are, it is control by mobile phone and if there is any obstacle in front of the machine while cutting grasses then the machine automatically create a beep sound. From time immemorial, the sun has been the major source of energy for life on earth. The solar energy was being used directly for purposes like drying clothes, curing agricultural produce, preserving food articles, etc. Even today, the energy we originate from fuel-wood, petroleum, paraffin, hydroelectricity and even our food originates obliquely from sun. Solar energy is almost unbounded. So here in our machine we used a energy source which never ends.